PENGARUH MODEL EKEE DENGAN MEDIA SUNO AI TERHADAP KREATIVITAS SISWA SD PELAJARAN SENI BUDAYA - Nasrullah Fitrotul Maghfiroh; Pance Mariati; Nafiah; Rudi Umar Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the effect of the digital-based EKEE learning model using Suno AI on improving elementary school students' creativity in Art and Culture subjects. A quantitative approach with a quasi-experimental nonequivalent control group design. Data were collected via pretests and posttests measuring fluency and originality indicators, then analyzed using IBM SPSS 25. The findings demonstrate that integrating the EKEE model with AI technology optimally enhances student creativity compared to conventional methods. This digital approach effectively fosters active student engagement in exploring, creating, and expressing original ideas, serving as an innovative learning alternative in the digital era.